Blood on the cross - Mark Davis (Asia Pacific Network, 2000)
An ABC Four Corners team investigates allegations about the role of the International Red Cross and the British military in a massacre in the Southern Highlands of Irian Jaya during May 1996. The story of what happened has never been told before.